KAJIAN POTENSI TERUMBU KARANG DI PANTAI TELUK LIMAU SEBAGAI DASAR RUMUSAN DAERAH PERLINDUNGAN LAUT KABUPATEN BANGKA - INDRA AMBALIKA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2008)
Inconventional Mining becomes more lustrous in Bangka since government gave a freedom to society in 2000 to mine tin. They mine not only on the ground but also in the coastal area, known as floating inconventional mining (TI Apung). This condition actually will destruct the coral reef ecosystem in the sea. Therefore, so many efforts should be done to keep and prevent the last coral reef ecosystem. One of them is to develop a good coral reef ecosystem into Marine Protection Area (MPA). This research is aimed to inventory the potential of coral reef ecosystem located in Teluk Limau Beach as a formulation base of MPA in Bangka. This activity was held from July 2007 till February 2008. It took the samples on July 2007, October 2007, and January 2008. The waters temperature was approximately 29OC and the salinity was approximately 33O/OO. Water pH tends to be alkali, meanwhile, the sediment pH is acid. Generally, this area has sand composition about 94,94% - 95,05% more than dust and clayey composition. Hard coral, Acropora Solitaryensis, has a solid value higher than others. Whereas, soft coral, Polyphyllia Talpina, is more dominant. Totally, both of them are about 73,9 % and coral mortality index is about 7,81%. An index of divercity coral community in Teluk Limau Beach is among 1,89484 – 2,0417. Homogeneous value (E) is about 0,58175 – 0,64411 and dominant value (D) is among 0,142722 – 0,195502. The potential of coral in Teluk Limau Beach can be developed as the Marine Protection Area in order to save the ecosystem from the pollution caused by floating inconventional mining.